The Goal Scale: A New Instrument to Measure the Perceived Exertion in Soccer (Indoor, Field, and Beach) Players - Polito, Luis Felipe Tubagi; Marquezi, Marcelo Luis; Marin, Douglas Popp; Villas Boas Junior, Marcelo; Brandão, Maria Regina Ferreira (Frontiers in Psychology, 2021)
The rating of perceived exertion (RPE) can be used to monitor the exercise intensity during laboratory and specific tests, training sessions, and to estimate the internal training load of the athletes. The aim of the present study was to develop and validate a specific pictorial perceived exertion scale for soccer players (indoor, field, and beach soccer) called GOAL Scale. The pictorial GOAL Scale (six drawings; 1 “low exertion” to 6 “exhaustion”) was validated for twenty under-17 soccer players (16.4 ± 0,68 yr; 175.4 ± 9 cm; 66.4 ± 7.7 kg; % fat mass 12.4 ± 3.3). In the validation phase, the athletes were evaluated in a progressive protocol involving stimuluses of three minutes with one minute for the rest into the stages until the voluntary exhaustion in Maximal Cardiopulmonary Effort Test (MCET), and in the Yo Yo Intermittent Recovery Test – Level 1 (Yo-Yo). The RPE identified by the GOL Scale, by the Borg Scale 6 – 20 and by the Cavasini Scale, as well as the heart rate (HR), perceptual of the heart rate (%HRmáx) and the blood lactate concentration ([La]) were immediately evaluated after each stage of both tests. Spearman’s correlation coefficient (p < 0,05) was used. Construct scale validity was examined by regressing GOAL Scale against Borg Scale 6 – 20 and Cavasini Scale and concurrent scale validity was investigated by regressing GOAL Scale against heart rate (HR), beats/min) and blood lactate concentration (mmol/L) during two progressive tests. There was a significant correlation values of the GOAL Scale with Borg Scale (r = 0.93; r = 0.88), Cavasini Scale (r = 0.91; r = 0.90), %HRmax (r = 0.91; r = 0,86), HR (r = 0.87; r = 0.83) and lactate (r = 0.68; r = 0.83) during tests (Maximal Incremental Cardiopulmonary Test and Yo-Yo test, respectively). The results evidenced concurrent and construct validity of the GOAL Scale across a wide range of exercise intensity. The absence of verbal anchors makes the use of this instrument to soccer, futsal and beach soccer athletes of different languages and different literacy levels possible.